A Correlational Study of Achievement Motivation and Pupils' Performance in the Standard Five Assessment Examination From Selected Schools in Selangor - Elias, Habibah; Long, Atan (1984)
The performance of pupils in the Primary Five Assessment Examination was examined in relation to a number of variables namely achievement motivation, socio-economic status, intelligence, area of residence, school milieu and parental encouragement to assess the correlation between them. The subjects were 90 pupils selected from 40 primary schools in Selangor and represented the Chinese, Malays and Indians. Individual interviews were conducted by the researcher. Subjects were asked to answer questionnaires, the Thematic Apperception Test, and the Raven's Progressive Matrices. The results showed that achievement motivation correlated highly with performance in the stated examination. The other variables which showed significant correlations with performance were socio-economic status, intelligence, school milieu and parental encouragement.